Risk Management оf Socially Responsible Activities: a Factor оf Strategic Competitiveness Management - OVSIENKO, N. V.; KOZYNETS, A. O. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2024)
Implementation of socially responsible practices comes with various risks affecting the competitive position of an enterprise. According to the European Commission, only 40% of companies have a systematic approach to managing corporate social responsibility risks, indicating a significant gap between declaring social responsibility and effective management of associated risks. For Ukrainian enterprises, the problem becomes particularly relevant in the context of European integration processes and the need to adapt to international business standards. The article substantiates the theoretical and methodological foundations of managing the risks of socially responsible enterprise activities as a factor in strategic competitiveness management. The main types of risks in socially responsible activities were analyzed: reputational, financial, compliance, operational, strategic risks, and the risk of greenwashing. A classification of corporate social responsibility (CSR) risks was developed with a description of possible consequences for enterprise competitiveness. A conceptual model for managing the risks of socially responsible activities in the strategic competitiveness management system is proposed, which includes five interconnected stages: risk identification, risk assessment, development of risk management strategies, implementation of mitigation measures, and effectiveness monitoring. The impact of digital transformation on CSR risk management processes was examined, particularly the application of big data technologies, artificial intelligence, and blockchain. Effective CSR risk management creates additional value for stakeholders and forms sustainable competitive advantages through increased trust, reduced volatility of performance results, and the formation of organizational capabilities. Companies with a proactive approach demonstrate 23% higher customer loyalty, 18% better financial results, and 31% lower stock price volatility compared to competitors.